De novo transcriptome assembly of sugarcane leaves submitted to prolonged water-deficit stress - Belesini, A. A. [UNESP]; Carvalho, F. M. S. [UNESP]; Telles, B. R. [UNESP]; Castro, G. M. de; Giachetto, P. F.; Vantini, J. S. [UNESP]; Carlin, S. D.; Cazetta, J. O. [UNESP]; Pinheiro, D. G. [UNESP]; Ferro, M. I. T. [UNESP] (Funpec-editora, 2017)
Sugarcane production is strongly influenced by drought, which is a limiting factor for agricultural productivity in the world. In this study, the gene expression profiles obtained by de novo assembly of the leaf transcriptome of two sugarcane cultivars that differ in their physiological response to water deficit were evaluated by the RNA-Seq method: drought-tolerant cultivar (SP81-3250) and drought-sensitive cultivar (RB855453). For this purpose, plants were grown in a greenhouse for 60 days and were then submitted to three treatments: control (-0.01 to -0.015 MPa), moderate water deficit (-0.05 to -0.055 MPa), and severe water deficit (-0.075 to -0.08 MPa). The plants were evaluated 30, 60, and 90 days after the beginning of treatment. Sequencing on an Illumina platform (RNA-Seq) generated more than one billion sequences, resulting in 177,509 and 185,153 transcripts for the tolerant and sensitive cultivar, respectively. These transcripts were aligned with sequences from Saccharum spp, Sorghum bicolor, Miscanthus giganteus, and Arabidopsis thaliana available in public databases. The differentially expressed genes detected during the prolonged period of water deficit permit to increase our understanding of the molecular patterns involved in the physiological response of the two cultivars. The tolerant cultivar differentially expressed a larger number of genes at 90 days, while in the sensitive cultivar the number of differentially expressed genes was higher in 30 days. Both cultivars perceived the lack of water, but the tolerant cultivar responded more slowly than the sensitive cultivar. The latter requires rapid activation of different water-deficit stress response mechanisms for its survival. This rapid activation of metabolic pathways in response to water stress does not appear to be the key mechanism of drought tolerance in sugarcane. There is still much to clarify on the molecular and physiological pattern of plants in response to drought.
Keywords: Drought; Gene expression; Saccharum spp.; RNA-Seq